Pengaruh Rekrutmen, Pelatihan, dan Pengembangan Karir Terhadap Kepuasan Kerja Karyawan di Iwaka Mart Pemogan - William Sentosa; Ketut Elly Sutrisni (Ikatan Da'i Indonesia, 2025)
This study aims to determine the effect of recruitment, training, and career development partially and simultaneously on employee job satisfaction. The sample in this study were 33 active employees at 4 Iwaka Mart Pemogan outlets. Data analysis techniques used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test, F Test, and t Test. From the results of the study, it was found that recruitment had a positive and significant effect on employee job satisfaction, training had a positive and significant effect on employee job satisfaction, and career development had a positive and significant effect on consumer impulsive buying. Suggestions that can be given by researchers are that companies are advised to create a clearer career structure, including promotion criteria, performance appraisal systems, and awards for high-achieving employees. Companies need to develop training programs that focus on improving employees' technical and soft skills, as well as expanding the variety of learning methods, such as on-the-job training, coaching, and mentoring.